Occupational exposure to blood and body fluids among health care workers in a teaching hospital in Mumbai, India - Singru Samir; Banerjee Amitav (Wolters Kluwer Medknow Publications, 2008)
Objective: Exposure to blood and body fluids is one of the hidden hazards faced by health care workers (HCWs). The objective of the present study was to estimate the incidence of such exposure in a teaching hospital. Materials and Methods: A cross-sectional study among a random sample of residents, interns, nurses and technicians ( n = 830) was carried out in a teaching hospital to estimate the incidence of exposure to blood and body fluids in the preceding 12-month period. Self-reported occurrence and the circumstances of the same were recorded by face-to-face interviews using a semi-structured questionnaire. Results: The response rate to the study was 89.76%. Occupational exposure to blood and body fluids in the preceding 12 months was reported by 32.75% of the respondents. The self-reported incidence was the highest among the nurses. Needle-stick injury was the most common mode of such exposures (92.21% of total exposures). Index finger and thumb were the commonest sites of exposure. Only 50% of the affected individuals reported the occurrence to concerned hospital authorities. Less than a quarter of the exposed persons underwent post-exposure prophylaxis (PEP) against HIV, although the same was indicated in about 50% of the affected HCWs based on the HIV status of the source patient. Conclusions: Occupational exposure to blood and body fluids was a common occurrence in the study sample. There was gross under-reporting of such incidents leading to a lack of proper PEP against HIV in 50% of those in whom the same appeared to be indicated.